2016
DOI: 10.1177/1687814016660287
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the influence of jetting equipment on the characteristics of centrifugal pump

Abstract: To reduce radial noises from the motor of centrifugal pumps, this study designed a water cooling system called jetting equipment to replace traditional fan cooling systems in pump motors. By measuring radiated noises, head, efficiency, and cavitation performance, the research compared the differences among experimental results of the original pump unit, the one with a normal design jetting pipe and another one with a larger jetting pipe. Results show that the radiated sound pressure level of the model pump was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Sі et. al [4] presented a method for improving the cavitation performances of the centrifugal pump by introducing a jet flow into the pump inlet device. However, the cavitation performances of the pump deteriorated with the increase of the flow rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sі et. al [4] presented a method for improving the cavitation performances of the centrifugal pump by introducing a jet flow into the pump inlet device. However, the cavitation performances of the pump deteriorated with the increase of the flow rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Ju et al, 2 cavitation in the automotive torque converter was numerically investigated using a well-known homogeneous cavitation model with experimental validations. In Si et al, 3 performances of jetting equipment were experimentally and numerically evaluated with its influences on the characteristics of centrifugal pumps. Cavitation performance of the pumps was tested along with other important characteristics.…”
Section: Fundamentals Of Cavitation and Bubble Dynamics With Engineermentioning
confidence: 99%
“…It stabilizes the fluid flow and provides its delivery with a uniform axial component of the absolute velocity in the flow cross-section. The flow structure in such an inlet casing in the overhung single stage pumps is analyzed in articles [8][9][10][11]. The authors found little uneven distribution of components of the absolute velocity with an increasing radius of a flow cross-section.…”
Section: Introductionmentioning
confidence: 99%